Giving the sense understanding and using Old Testament historical texts - Howard, David Morris, Jr, 1928-; Grisanti, Michael A. (Leicester, UK Apollos, 2003)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. -- history of contemporary events -- primary sources; Bible. O.T. -- criticism, interpretation, etc